PRECONCEPTIONAL TRANSABDOMINAL CERVICAL CERCLAGE: CASE REPORT OF A WOMAN WITH SIX FAILED TRANSVAGINAL CERCLAGES - Negash Abdella, Mustefa; Curran, Diana; Bekele, Delayehu (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT Preconception transabdominal cervicoisthmic cerclage is a safe and effective option for selected group of patients with cervical insufficiency and have failed conventional conceptional cervical cerclages or with severely damaged cervix. We present here a preconception transabdominal cervicoisthmic cerclage which was placed by laparotomy for a woman with six failed conceptional transcervical cerclages with recurrent late second trimester pregnancy losses. The woman conceived spontaneously and delivered at term with an alive male healthy new born with no maternal and fetal complications. A brief discussion of the indication, procedure and complications of Preconception transabdominal cervicoisthmic cerclage is also included. KEY WORDS: Transabdominal cerclage, Cervical insufficiency, Recurrent pregnancy loss